Effect of open minimally invasive parathyroidectomy in the management of primary hyperparathyroidism - Kumar, Sistla Raj; Lakshmi, Kantamneni Baby; Reddy, Kandula Venkata Teja; Deepika, B. Anu; Teja, V. Viswa (International Surgery Journal, 2017)
Background: To compare the patients who underwent open minimally invasive parathyroidectomy (OMIP) and conventional surgical approach for primary hyperparathyroidism. Methods: 50 patients with documented primary hyperparathyroidism who underwent surgery by single surgeon, 25 patients who underwent more conventional neck exploration for parathyroidectomy were chosen to match the OMIP patients. Patient demographics, preoperative calcium and parathyroid hormone levels, operative time, total time in the operating room, time in the recovery room, complications, hospital charges for the operating room, and total hospital charges were analyzed. Results: There was no statistical difference in demographics between the groups. By definition, all patients in the OMIP group and control group are of primary hyperparathyroidism. Mild hypercalcemia in both groups, only 16% of patients in the OMIP group and only 12% in the standard group were considered asymptomatic. The three most common presentations in both groups were fatigue (52% in the OMIP group, 60% in the standard group), renal stones (36% OMIP, 40% standard) and decreased bone density (48% OMIP, 52% standard). Operative time, total time in the operating room, and time in the recovery room were all significantly decreased in the OMIP group. No specific complications observed in both groups. Length of hospital stay and hospital charges are very much significant in both groups. OMIP group has less hospital stay and cost effective. Conclusions: OMIP technique resulted in excellent cure rates for primary hyperparathyroidism while simultaneously decreasing operative time and hospital stays. These resulted in significant cost reductions without compromising patient safety.